Prenatal education: profile and expectations of the couples. - Moreira, Rosa Maria Santos (2016)
Develop the capacities of women/couples to stay healthy during pregnancy, becoming aware of the rights, needs and potential problems of maternal and newborn health is a challenge for nurses and midwives who work with this population (Departamento de Reducir los Riesgos del Embarazo 2010). Prenatal education is a good strategy to meet the needs of pregnant women/couples, to improve outcomes in health and community development (Svenson, Barclay & Cooke 2006). Knowing the profile and expectations of the participants in these prenatal education groups, improves the quality of prenatal education programs and enables higher qualification of the professionals who promote them.